Multiphoton-FLIM quantification of the EGFP-mRFP1 FRET pair for localization of membrane receptor-kinase interactions. - Peter, M; Ameer-Beg, S; Hughes, M; Keppler, MD; Prag, S; Marsh, M; Vojnovic, B; Ng, T (2005)
We present an improved monomeric form of the red fluorescent protein, mRFP1, as the acceptor in biological fluorescence resonance energy transfer (FRET) experiments using the enhanced green fluorescent protein as donor. We find particular advantage in using this fluorophore pair for quantitative measurements of FRET using multiphoton fluorescence lifetime imaging microscopy (FLIM). The technique was exploited to demonstrate a novel receptor-kinase interaction between the chemokine receptor (CXCR4) and protein kinase C (PKC) alpha in carcinoma cells for both live- and fixed-cell experiments. The CXCR4-EGFP: PKCalpha-mRFP1 complex was found to be localized precisely to intracellular vesicles and cell protrusions when imaged by multiphoton fluorescence-FLIM. A comparison of the FRET efficiencies obtained using mRFP1-tagged regulatory domain or full-length PKCalpha as the acceptor revealed that PKCalpha, in the closed (inactive) form, is restrained from associating with the cytoplasmic portion of CXCR4. Live-cell FLIM experiments show that the assembly of this receptor:kinase complex is concomitant with the endocytosis process. This is confirmed by experimental evidence suggesting that the recycling of the CXCR4 receptor is increased on stimulation with phorbol ester and blocked on inhibition of PKC by bisindolylmaleimide. The EGFP-mRFP1 couple should be widely applicable, particularly to live-cell quantitative FRET assays.